Karakteristik Pasien Penderita Apendisitis Akut di RSUD Sanjwiani, Gianyar: Apendisitis akut - MASYENI, SRI; SANJAYA LIE, MIRACLE NYOMAN; WIJAYA, INDRA (Universitas Hang Tuah, 2024)
Acute appendicitis is one of the most common emergency surgical cases of lower right abdominal pain, a small proportion of cases in emergency units in the world which are often experienced by children and adults. This study aims to identify the characteristics of acute appendicitis in patients at Sanjiwani Hospital, Gianyar. This research is a descriptive study with a retrospective cross-sectional approach method that uses secondary data in the form of medical records of acute appendicitis patients who underwent examinations at Sanjiwani Regional Hospital, Gianyar in the period 1 January 2020–31 December 2022. The results showed that the highest number of acute appendicitis sufferers were aged 10–19 years (34.3%), with the highest incidence in males (60.6%), and the most symptoms found, namely lower right abdominal pain (100%), with the most positive examination of the Mc Burney Sign (89.9%) and increased white blood cells with an average of 12.8 x 10^3/uL.